KEBIJAKAN KRIMINAL DALAM PENANGGULANGAN TINDAK PIDANA JUDI ONLINE YANG DILAKUKAN MARKAS BESAR KEPOLISIAN REPUBLIK INDONESIA (MABES POLRI) - Maria Margaretta Sitompul; Madiasa Ablisar; Muhammad Hamdan; Jelly Leviza (USU LAW JOURNAL, 2014)
ABSTRACT Criminal act of gambling is set up in a variety of regulations in Indonesia, namely Article 303 of the Criminal Code, 303 bis of the Criminal Code, Law no. 7 of 1974 on Gambling Control. In particular online gambling regulated in Article 27 paragraph (2) of the Act ITE. Coverage gambling within the context of Article 27 paragraph (2) of the Act ITE are in the context of Article 303 bis of the Penal Code and Article 303 of the Criminal Code.  In the investigation of online gambling, the investigator based Act ITE and Criminal Procedure Code. Countermeasures of online gambling in penal done with arrest, detention, search and seizure. Countermeasures non-penal done by cyber patroling. There are several inhibiting factors in Countermeasures the crime of gambling online, inhibiting factor in terms of the law, which is where the investigator difficulty of implementing Article 43 paragraph (6) of the Act ITE., lack of quality and quantity of investigators. not given compensation as a form of tribute to the investigator for his achievements. Terms of the legal culture of society is the number of Indonesian society in the category of poor, high unemployment, cultural lazy to earn money with a short path with gambling. gambling has become a tradition in many areas. Keywords: criminal policy, countermeasures, criminal act, online gambling